P118: Older adults in the emergency department: a retrospective cross-sectional study of the geriatric population in Edmonton emergency departments. (May 2019) - Morch, K.; Schonnop, R.; Gauri, A.; Ha, D.
Abstract : Introduction : The geriatric patient population accounts for an ever increasing proportion of emergency department (ED) visits. Geriatric centered EDs are an emerging area of interest and research. Though there have been past studies looking at older patient presentations at individual hospitals, there is limited data describing geriatric presentations within an entire Canadian geographic health region. This study characterizes the population of older adults utilizing the EDs in the Edmonton Zone, a health region that comprises a total of eleven tertiary (T), urban community (UC) and rural community (RC) hospitals.Methods : This retrospective cross-sectional study targeted all patients ≥65 years presenting to the Edmonton Zone EDs between April 1, 2017 to March 31, 2018. Data was extracted from the Emergency Department Information System (EDIS) database for ten EDs in the health region. Clinical and administrative data points were extracted and examined for each site.Results : We analyzed 100, 813 ED geriatric patient visits during our study period, accounting for 18.7% of total ED visits to the Edmonton Zone. The five most common triage complaints at ED presentation were shortness of breath, abdominal pain, chest pain with cardiac features, general weakness, and back pain. CTAS scores 1-3 were assigned to 77.8% of geriatric presentations (T: 86.3%, UC: 77.4%, RC: 60.9%). 27.3% of geriatric patients had presented to an ED within the past 30 days (T: 30.0%, UC: 25.4%, RC: 27.7%). On average, 35.3% of older adult ED visits involved a consultation (T: 51.7%, UC 30.8%, RC 14.6%) and approximately 25% of geriatric patients were admitted to hospital during their ED visit (T: 42.8%, UC: 19.4%, RC: 7.1%). The average length of stay (LOS) in the ED (hh:mm) was 10:19 (T: 10:24, UC: 11:38, RC: 5:43). Overall, 2.4% of all geriatric patients left an ED without being seen after initial registration (T: 2.7%, UC: 2.2%, RC: 2.1%).Conclusion : Older adults represent a significant proportion of the ED visits in the Edmonton Zone. The triage acuity, LOS, re-presentation, consultation and admission rates varied based on the type of ED, which has implications for resource allocation within the health region. Our results can also direct future targeted initiatives and quality improvement projects to the various types of EDs in the Edmonton Zone, and facilitate planning of ED services for older adults in other health regions who have a similar geographic distribution of care sites.